2012
DOI: 10.1155/2013/716098
|View full text |Cite
|
Sign up to set email alerts
|

Effective Biosorption of Nickel(II) from Aqueous Solutions Using Trichoderma viride

Abstract: The primary objective of the present study is to evaluate the optimization conditions such as kinetic and equilibrium isotherm models involved in the removal of Ni(II) from the aqueous solutions byTrichoderma viride. The biosorbent was characterized by FTIR and SEM. The optimum biosorption conditions were determined as a function of pH, biomass dosage, contact time, initial metal ion concentration, and temperature. The maximum Ni(II) biosorption was obtained at pH 4.5. The equilibrium data were better fit by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…It was also observed that effects of Ni was more pronounced than Co. Results are in agreement with the work of Sujatha et al (2013) who documented that the surface modifications occurred after binding of Ni(II) ions onto the surface of Trichoderma viride biomass. In a similar study Chakravarty and Banerjee (2008) reported that there was a clear change (rough cell surface and membrane indentations) in the outer surface of Acidophilic bacterium under metal stress condition.…”
Section: Discussionsupporting
confidence: 91%
“…It was also observed that effects of Ni was more pronounced than Co. Results are in agreement with the work of Sujatha et al (2013) who documented that the surface modifications occurred after binding of Ni(II) ions onto the surface of Trichoderma viride biomass. In a similar study Chakravarty and Banerjee (2008) reported that there was a clear change (rough cell surface and membrane indentations) in the outer surface of Acidophilic bacterium under metal stress condition.…”
Section: Discussionsupporting
confidence: 91%
“…These properties have made Trichoderma a omnipresent genus able to grow in wider habitats and at high population densities (Chet et al, 1997;Chaverri et al, 2011). There is a numerous literature available on Trichoderma research but recent updates in cooperation with longestablished facts are not summarized in past few years (Gal-Hemed et al, 2011;Sujatha et al, 2013). This review focuses on the occurrence of Trichoderma spp., their mode of action, commercial production techniques with applications in agriculture and use in sustainable environmental practices.…”
Section: Trichoderma -A Multifaceted Fungusmentioning
confidence: 99%
“…The application of microorganisms as biosorbents has several advantages due to their small size and the ability to adsorption, binding the concentrations of heavy metals from aqueous solutions including very dilute concentrations by certain types of inactive, dead and living microbes [7]. The same microorganisms with other microbial groups can accumulate metals from their external environment by of physics-chemistry and biological mechanisms [8]. In this process, the uptake of heavy metals occurs as a result of physico-chemical interactions of metal ions with the cellular compounds of biological species.…”
Section: Introductionmentioning
confidence: 99%
“…The capacity of T. viride to adsorp metal ions has been studied before [8], and results showed that T. viride effectively adsorbed Ni 2+ from the aqueous solution. Another study has been conducted [9], and the results indicated that T. viride had the capacity to adsorp Cr(VI), the adsorption model followed Langmuir model and Freudlich isotherm.…”
Section: Introductionmentioning
confidence: 99%